Experimental research of LNG accidental underwater release and combustion behavior. (March 2020) - Zhang, Yixiang; Zhu, Jianlu; Teng, Lin; Song, Cunyong; Li, Yuxing
Abstract: Evaluating potential hazards caused by accidental LNG release from underwater pipelines or vessels is a significant consideration in marine transportation safety. The aim of this study was to capture the dynamic behavior of LNG jet released under water and to analyze its vapor dispersion characteristics and combustion characteristics on the water surface during different release scenarios. Controlled experiments were conducted where LNG was jet released from a cryogenic storage tank. The dynamic process of LNG being jet released from orifices of different sizes and shapes, as well as the rising plume structure, were captured by a high-speed camera. The leakage flow rate and pipeline pressure were recorded by a flow meter and pressure gauge, respectively. The concentration distribution that emanated from the water surface was measured utilizing methane sensors in different positions with various wind speeds. The flame combustion characteristics of LNG vapor clouds, which immediately ignited upon the enclosed water tank, were also recorded. Additionally, the mass burning rate of the flame on the water surface was evaluated, and a new correlation between the ratio of flame length and width was established. The results indicated a large dimensionless heat release rate ( Q *) and a continuous release flow rate in a limited burning area. This study could provide greater understanding of the mechanisms of LNG release and combustion behavior under water. Graphical abstract: Image 1 Highlights: Experimental investigation of LNG leakage underwater and combustion behavior on the water surface in a wind tunnel. Liquid living column and dynamic behavior of ice column periodicity breakup was observed by a high-speed camera. Dimensionless relationships was established to evaluate the mass burning rate and flame geometry on the water surface.